Altered Pasts: Counterfactuals in History - Evans, Richard J. (London Little Brown, 2014)
A bullet misses its target in Sarajevo, a would-be Austrian painter gets into the Viennese academy, Lord Halifax becomes British prime minister in 1940: seemingly minor twists of fate on which world-shaking events might have hinged.Alternative history has long been the stuff of parlour games, war-gaming and science fiction, but over the past few decades it has become a popular stomping ground for serious historians. Richard J. Evans now turns a critical, slightly jaundiced eye on the subject. Altered Pasts examines the intellectual fallout from historical counterfactuals. Most importantly, Evans takes counterfactual history seriously, looking at the insights, pitfalls and intellectual implications of changing one thread in the weave of history.
Keywords: Historiography